PENGARUH ROA, DER, SIZE DAN SALES GROWTH TERHADAP TAX AVOIDANCE DENGAN AUDIT COMMITTE SEBAGAI PEMODERASI - Diksen Pahala; J. M.V. Mulyadi; Darmansyah , (Fakultas Ekonomi dan Bisnis Islam, 2021)
Introduction: The purpose of this study was to determine the effect on tax avoidance by using return on assets, debt to equity ratio, size, sales growth and audit committee as moderating variables. Background Problems: Tax avoidance carried out by taxpayers, especially entities in the form of Tax Avoidance, is in this case not in conflict with applicable laws or legal provisions, because it is considered that practices related to Tax Avoidance are more about exploiting loopholes in the Law Research Methods: The data used is data from 21 hotel companies listed on the Indonesia Stock Exchange in 2015-2019. Data analysis using Moderated Regression Analysis. Results: The results showed that ROA has an effect on Tax Avoidance, and ROA is influenced by the Audit Committee as quasi moderation also strengthens Tax Avoidance. DER has an effect on Tax Avoidance, and DER is influenced by the Audit Committee as quasi moderation and also strengthens Tax Avoidance. SIZE has an effect on Tax Avoidance, and SIZE is influenced by the Audit Committee as quasi moderation also strengthens Tax Avoidance. Sales Growth does not affect to Tax Avoidance, and Sales Growth is not influenced by the Audit Committee as moderation to Tax Avoidance. Conclusion:. audit committee can moderate roa, der, size. Meanwhile, the audit committee was unable to moderate sales growth.